Parental body dissatisfaction and controlling child feeding practices: A prospective study of Australian parent-child dyads. (January 2019) - Webb, Haley J.; Haycraft, Emma
Abstract: The aim of the present study was to examine whether parents' reported use of controlling feeding practices (restrictive feeding and pressure to eat) change over 6 months, and whether parents' concerns about their own weight and shape are prospectively associated with increasing use of controlling feeding practices. Participants were 48 Australian parents (92% female; M age = 37.8 years) who completed questionnaires twice, with a 6-month time lag, regarding a target child aged 7.6 years on average (52% female). Results revealed that, in general, parental feeding practices and body dissatisfaction showed little change over 6 months. As expected, parental body dissatisfaction predicted increased use over time of restrictive feeding practices for the purpose of managing child weight, but (unexpectedly) not restrictive feeding for child health or pressure to eat. The findings provide key evidence that parents who use higher levels of controlling feeding practices are likely to continue to do so over time, and that parental body dissatisfaction poses a small but significant risk for parents' increasing use of restrictive feeding for management of child weight. The present findings support suggestions that the connection between parent body dissatisfaction and maladaptive feeding practices play a role in the intergenerational transmission of body image and eating pathology. Highlights: Pressure to eat and restrictive feeding showed rank order consistency over 6 months. No mean-level differences over time for pressure to eat and restriction for health Mean-level differences (i.e., decline) over time found for restriction for weight Parent body dissatisfaction predicted greater restrictive feeding for child weight. Parent body dissatisfaction was not related to pressure or restriction for health.